A CRITICAL ANALYSIS OF GARBHAVRIDHI (GROWTH OF EMBRYO/FETUS) IN THE THREE TRIMESTERS (AYUSHDHARA, 2017)
The union of Sukra (sperm) and Sonita (ovum) along with Atma (soul) in Garbhashaya (uterus) is termed as Garbha (embryo/fetus). It is formed as a result of combination of Panchamahabhutas (five elements) and Chetana (soul). Further these Panchamahabhutas (five elements) play an important role in Garbhavridhi (growth of embryo/fetus). Almost all Acharyas (scholars) of Ayurveda has similar opinion regarding the formation of Garbha (embryo/fetus). Four Garbhotpadakabhavas (factors responsible for the formation of embryo/ fetus) and six Garbhavridhikarabhavas (factors responsible for the development of embryo/fetus) aid in the formation and growth of Garbha (embryo/fetus). The developmental stages of Garbha (embryo/fetus) have been vividly narrated in Ayurveda as well as modern science. Almost all ancient scholars have described the month wise development of Garbha (embryo/fetus) but Harita has keenly observed the changes happening in weeks or a couple of days at a few instances. The concept of Garbhavridhi (growth of embryo/fetus) was of great interest to the Ayurvedic scholars; the developmental changes happening in the embryo during pregnancy is given much importance in modern parlance too. As per modern view the whole period of pregnancy can be divided into three trimesters each of which comprises of three months. Each trimester has its own milestones in the developmental aspect of embryo/fetus. The knowledge regarding the developmental events help in preventing various fetal anomalies thus aids in the formation of healthy individuals and thereby a healthy society. The basic facts pertaining to the growth, differentiation, specialization and development of an individual starting from fertilization till birth forms the core concept of this review. A keen study of both Ayurvedic and modern aspects of the developmental events during the gestational period has been attempted for a better understanding.